2012
DOI: 10.1080/17441692.2012.736681
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of AIDS movements on the policy responses to HIV/AIDS in Brazil and South Africa: A comparative analysis

Abstract: Brazil and South Africa were among the first countries profoundly impacted by the HIV/AIDS epidemic and had similar rates of HIV infection in the early 1990s. Today, Brazil has less than 1% adult HIV prevalence, implemented treatment and prevention programmes early in the epidemic, and now has exemplary HIV/AIDS programmes. South Africa, by contrast, has HIV prevalence of 18% and was, until recently, infamous for its delayed and inappropriate response to the HIV/ AIDS epidemic. This article explores how differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…Patient engagement in healthcare has been a concern of a series of societal movements and civil rights groups since the 1960s, including the Black/African American Civil Rights Movement for autonomy [1], the Women's Health Movement, with its a primary goal of improving health care for all women [2], the Physical Disabilities Movement, which demands equal treatment and access to health care for people with disabilities [3] [4], and the AIDS Movement, which promotes equitable access to treatment, care and prevention services and has launched anti-stigma and education campaigns [5]. The common concern shared by such movements is the importance of consumerism, and the need for a transition from patients as passive recipients of health care to their more active collaboration and taking control of their own health.…”
Section: Introductionmentioning
confidence: 99%
“…Patient engagement in healthcare has been a concern of a series of societal movements and civil rights groups since the 1960s, including the Black/African American Civil Rights Movement for autonomy [1], the Women's Health Movement, with its a primary goal of improving health care for all women [2], the Physical Disabilities Movement, which demands equal treatment and access to health care for people with disabilities [3] [4], and the AIDS Movement, which promotes equitable access to treatment, care and prevention services and has launched anti-stigma and education campaigns [5]. The common concern shared by such movements is the importance of consumerism, and the need for a transition from patients as passive recipients of health care to their more active collaboration and taking control of their own health.…”
Section: Introductionmentioning
confidence: 99%
“…A particular focus is on whether TASO has managed to improve service delivery, not only directly 1 -by providing services the state lacked the capacity to provide -but also by 'holding government to account' on HIV/AIDS policy and service provision. It has been suggested that civil society did so in South Africa and Brazil (Nunn et al, 2012), through various approaches including litigative strategies (Meier and Yamin, 2011). The analysis reported in this paper bears out neither a story of exemplary leadership from the Museveni government nor of civil society 'holding government to account'.…”
Section: Introductionmentioning
confidence: 95%
“…in Nunn et al, 2012). However, this analysis is too simplistic to enable a sufficient understanding of the AIDS response in Uganda, where 2 Informed consent was obtained from all informants.…”
Section: 'Aids Leadership' and Coalition-buildingmentioning
confidence: 99%
“…The country's actions in the international realm stemmed from its normative commitment to health as a human rights issue and efforts to defend a domestic social program (Flynn, 2013a;Nunn, Dickman, Nattrass, Cornwall, & Gruskin, 2012). A broad-based treatment coalition pushed for international resolutions at the World Health Organization and other UN agencies to define access to medicines as a human right and gained attention in international media.…”
Section: Normative Frameworkmentioning
confidence: 99%